Hearing Voices: Reapproaching Medieval Inquisition Records - Zbíral, David (Religions, 2022)
The records of medieval heresy inquisitions have been a subject of controversy ever since their rediscovery by historians. The detail they convey of specific social interactions has continued to inspire generations of scholars, while the coercive conditions of their production have placed strong caveats over their interpretation. This article offers a comprehensive review of the debate on the uses of inquisition records, encompassing scholarship across multiple languages and schools of thought. It also highlights some shortcomings in that debate, e.g., the overrepresentation of inquisitors’ choices; the claim that the use of torture led automatically to reproducing outlandish inquisitorial fears; and the idea that exceptional detail correlates with reliability. The article concludes with the proposal of the Dissident Networks Project (DISSINET) to use structured data within a new variety of quantitative history. This method, founded on the Computer-Assisted Semantic Text Modelling approach that DISSINET has pioneered, is well-suited to addressing the biases of inquisition documents and opening them to scrutiny, thus providing a significant complement to close reading.